Find the composite function, then find (f x g) (-1) SHOW WORK

Mathematics
Tutor: None Selected Time limit: 1 Day

Oct 9th, 2015

Thank you for the opportunity to help you with your question!

(f0g)(x)=f(g(x))=4(x-2)^2+9=4(x^2-4x+4)+9=4x^2-16x+16+9=4x^2-16x+25

(f0g)(-1)=4(-1)^2-16*(-1)+25=4+16+25=45

Please let me know if you need any clarification. I'm always happy to answer your questions.
Oct 9th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Oct 9th, 2015
...
Oct 9th, 2015
Feb 25th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer